2017
DOI: 10.3892/ol.2017.5819
|View full text |Cite
|
Sign up to set email alerts
|

Silencing TAK1 alters gene expression signatures in bladder cancer cells

Abstract: Abstract. The aim of the present study was to identify the differentially expressed genes (DEGs) that are induced by the silencing of transforming growth factor-β-activated kinase 1 (TAK1) in bladder cancer cells and to analyze the potential biological effects. Dataset GSE52452 from mutant fibroblast growth factor receptor 3 (FGFR3) bladder cancer cells transfected with control siRNA or TAK1-specific siRNA was downloaded from Gene Expression Omnibus. The DEGs between the two groups were identified using Limma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…There are some studies reported their involvement in cancer biology. For example, KCND2 upregulation was associated with cancer stem cell properties of neuroblastoma cells, 35 KCND2 was also considered as a hub gene in the complex metabolic network of bladder cancer 36 . One recent study found that KCND2 upregulation was a valuable prognostic biomarker in gastric cancer patients 37 .…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies reported their involvement in cancer biology. For example, KCND2 upregulation was associated with cancer stem cell properties of neuroblastoma cells, 35 KCND2 was also considered as a hub gene in the complex metabolic network of bladder cancer 36 . One recent study found that KCND2 upregulation was a valuable prognostic biomarker in gastric cancer patients 37 .…”
Section: Discussionmentioning
confidence: 99%
“…PTHLH functions as a critical regulator of cellular and organ growth, development, migration, survival and of epithelial calcium ion transport (45). Recently, Chen et al revealed that silencing of transforming growth factor-b-activated kinase 1 (TAK1) in BC cells promote the development of cancer cells by upregulating PTHLH (46). CTSE is involved in antigen processing and the maturation of secretory proteins, which can regulate the processing of antigenic peptides during MHC class II-mediated antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to underline that arsenite trioxide has been reported to induce the phosphorylation of RXRA, subsequent to oxidative damages and the activation of the stress-activated protein kinases cascade 48 . MAP3K7 was reported to be down-regulated in BlC and PrC 49 . NR3C1 resulted to be down-regulated in KiC as well as in BlC 50 , 51 and its NR3C1 polymorphism was associated to PrC risk 52 .…”
Section: Discussionmentioning
confidence: 99%